2017
DOI: 10.1093/hmg/ddx320
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 G2019S-induced mitochondrial DNA damage is LRRK2 kinase dependent and inhibition restores mtDNA integrity in Parkinson’s disease

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) are associated with increased risk for developing Parkinson's disease (PD). Previously, we found that LRRK2 G2019S mutation carriers have increased mitochondrial DNA (mtDNA) damage and after zinc finger nuclease-mediated gene mutation correction, mtDNA damage was no longer detectable. While the mtDNA damage phenotype can be unambiguously attributed to the LRRK2 G2019S mutation, the underlying mechanism(s) is unknown. Here, we examine the role of LRRK2 kinase fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 59 publications
8
78
0
1
Order By: Relevance
“…Other groups have also reported higher mtDNA damage in LRRK2 in vitro and in vivo models . We agree with the authors that their results support mtDNA damage as a promising biomarker of PD risk and progression in LRRK2 patients and suggest additional aspects of LRRK2 PD that are worthy of further investigation.…”
supporting
confidence: 91%
“…Other groups have also reported higher mtDNA damage in LRRK2 in vitro and in vivo models . We agree with the authors that their results support mtDNA damage as a promising biomarker of PD risk and progression in LRRK2 patients and suggest additional aspects of LRRK2 PD that are worthy of further investigation.…”
supporting
confidence: 91%
“…Fewer than 12% (8/67) of published studies used more than ten cell lines ( Fig. 3d) 37,42,56,70,79,84,92 . Interestingly, it has been estimated that sample sizes of 10-30 individuals per hiPSC study may be required to achieve a statistical power of 80%, assuming that the cellular readouts variance is high and the disease effect is small (>0.7 relative heterogeneity, which is the ratio between within-group standard deviation and mean group difference) 189 .…”
Section: Studies Of Pd With Patient-derived Ipscsmentioning
confidence: 99%
“…In this respect, alterations in glutamatergic transmission in striatal slices from G2019S-LRRK2 transgenic animals were only observed when rotenone, a mitochondrial toxin, was also present, indicating that LRRK2 might only play a role in the diseased state, such as impaired DAergic neurotransmission (Tozzi et al, 2018). In support, recent studies have suggested that LRRK2 kinase activity is increased in substantia nigra in the AAV-␣-synuclein overexpression model and in rotenone models as well as in postmortem tissue from idiopathic PD patients (Howlett et al, 2017;Di Maio et al, 2018).…”
Section: Discussionmentioning
confidence: 75%